SPACE AND TIME: ANALYZING COMIC PANELS ON KOMIKALISASI HUJAN BULAN JUNI - Faisal, Dini; Pramesti, Utami Dewi; Rasyid, yulianti (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2018)
Hujan Bulan Juni is a short comic illustrated by Mansjur Darman. It is a modified form of literary works from poetry text into comic. Converting the written language into a visual language can provide different understanding and reading experience because the visual language uses its own distinct and interesting